(untitled) (Eurasian Journal of Philology Science and Education, 2018)
In the article, the traditional grammar is distinguished from the notion of history, not just in the context of history, but also from point of view structured grammar. Actuality of the theme of the article – is the definition of the fundamental and the functional directions of fundamental accents. It has been revealed that these two directions are based on two separate points of origin and that grammar of a separate grammar is being studied in the direction «from the value to the tool index», and the functional grammar is being studied in the direction «from device to value». If traditional grammar analyzes structured suggestions, functional grammar can be used for the purpose of intelligent structures. In the article, we have differentiated between individual and functional grammar, which is considered in the linguistic aspect as one of the main components of each other’s development.